Analysis of Organizational Culture at PT. Bank Sumut Conventional Sub-Branch Office Medan - Dina Annisa Rambe, Harmein Nasution, Linda Trimurni Maas (Pusdikra Publishing, 2022)
Within the organization, values are a source of strength, energy and motivation that can unite various views on behavior in order to form a strong organizational culture. One way to measure the effectiveness of a company's organizational culture is to use the Organizational Culture Assessment Instrument (OCAI). This study aims to analyze the dominant type of organizational culture and to evaluate the type of organizational culture expected by the employees of PT Bank Sumut Conventional Sub-Branch Office Medan. Sampling in this study using the Nonprobability sampling method with the Accidental Sampling technique , the number of samples that will be used as respondents in this study is 144 people. The results of this study show that the current dominant cultural profile is a culture that focuses on emphasizing innovation, creativity, and the discovery of something new, namely the Adhocracy culture and for the cultural profile that is expected to be dominant in the future is a culture that focuses on human resource development, loyalty and function of the company as a family, namely the Clan culture. This cultural profile picture can be used as a company for policy making in accordance with the vision, mission, and goals of PT Bank Sumut Conventional Sub-Branch Office Medan Region